Current status and future prospects of transforming growth factor‐β as a potential prognostic and therapeutic target in the treatment of breast cancer. Issue 5 (22nd January 2019) - Amerizadeh, Forouzan; Bahrami, Afsane; Khazaei, Majid; Hesari, AmirReza; Rezayi, Majid; Talebian, Sahar; Maftouh, Mona; Moetamani‐Ahmadi, Mehrdad; Seifi, Sima; Shahidsales, Soodabeh; Joudi‐Mashhad, Mona; Ferns, Gordon A.; et al.
Abstract: The transforming growth factor‐β (TGF‐β) signaling pathway is one of the important pathways involved in the cancer cell proliferation, invasion, migration, angiogenesis, apoptosis, as well as in metastasis by agitation or invasion of metastasis‐related factors, including matrix metalloproteinase (MMP), epithelial‐to‐mesenchymal transition (EMT), tumor microenvironment (TME), cancer stem cells (CSCs), and cell adhesion molecules (CAMs). These data suggest its potential value as a therapeutic object in the treatment of malignancies including breast cancer. Several pharmacological approaches have been established to suppress TGF‐β pathway; such as vaccines, small molecular inhibitors, antisense oligonucleotides, and monoclonal antibodies. Some of these are now approved by the US Food and Drug Administration for targeting the TGF‐β signaling pathway. This study attempts to summarize the current data about the functions of TGF‐β in cancer cells, and their probable application in the cancer therapy with a specific emphasis on recent preclinical and clinical research in the treatment of breast cancer and its prognostic value.